TO DESIGN A COMPREHENSIVE ENGINEERING TRAINING MODULE USING SWANSOFT CNC SIMULATOR - Ramli, Amir Qayyum (IRC, 2021)
This project focuses on the analysis of the use of Computer Numerical Control (CNC) simulation software and its component.